Characterization of rare spontaneous human immunodeficiency virus viral controllers attending a national United Kingdom clinical service using a combination of serology and molecular diagnostic assays - Khan,M; Bradshaw,D; Brown,CS; Haddow,J; Patel,P; Tosswill,JHC; Pollock,K; Elliott,T; Wang,X; Alagaratnam,J; Mora-Peris,B; Kaye,S; et al. (Open Forum Infectious Diseases, 2023)
BACKGROUND: We report outcomes and novel characterization of a unique cohort of 42 individuals with persistently indeterminate human immunodeficiency virus (HIV) status, the majority of whom are HIV viral controllers. METHODS: Eligible individuals had indeterminate or positive HIV serology, but persistently undetectable HIV ribonucleic acid (RNA) by commercial assays and were not taking antiretroviral therapy (ART). Routine investigations included HIV Western blot, HIV viral load, qualitative HIV-1 deoxyribonucleic acid (DNA), coinfection screen, and T-cell quantification. Research assays included T-cell activation, ART measurement, single-copy assays detecting HIV-1 RNA and DNA, and plasma cytokine quantification. Human immunodeficiency virus seropositivity was defined as ≥3 bands on Western blot; molecular positivity was defined as detection of HIV RNA or DNA. RESULTS: Human immunodeficiency virus infection was excluded in 10 of 42 referrals, remained unconfirmed in 2 of 42, and was confirmed in 30 of 42, who were identified as HIV elite controllers (ECs), normal CD4 T-cell counts (median 820/mL, range 805-1336), and normal CD4/CD8 ratio (median 1.8, range 1.2-1.9). Elite controllers had a median duration of elite control of 6 years (interquartile range = 4-14). Antiretroviral therapy was undetected in all 23 subjects tested. Two distinct categories of ECs were identified: molecular positive (n = 20) and molecular negative (n = 10). CONCLUSIONS: Human immunodeficiency virus status was resolved for 95% of referrals with the majority diagnosed as EC. The clinical significance of the 2 molecular categories among ECs requires further investigation.